PC ‘Aisyiyah Ngampilan institutional strengthening through effective organizational communication - Adhianty Nurjanah; Nano Prawoto (Universitas Muhammadiyah Magelang, 2023)
The organizational problem of ‘Aisyiyah Branch Leadership (PCA) Ngampilan is the diversity of the community which is often referred to as the